CO2 Sequestration Using Sodium Hydroxide and Its Utilization for Chlorella sorokiniana Biomass Production (Biosaintifika: Journal of Biology & Biology Education, 2022)
Chlorella is widely used for its fast growth rate and easy cultivation with 14–30% lipid content and 36–59% dry weight. Thus, sodium hydroxide is used to increase carbon consumption, biomass, and metabolites productions in microalgae. This study was conducted to observe the effect of sodium hydroxide addition on biomass and metabolites  production in photoautotrophic cultivated Chlorella sorokiniana. Microalgae C.sorokiniana (LIPI12-Al016) was obtained from the culture collection of Microalgae and Bioprocess Engineering Research Group laboratory, National Research and Innovation Agency. Then, the microalgae were cultivated in media with various concentrations of sodium hydroxide. Biomass production was measured by gravimetry, and carbon consumption was measured by acid-alkalimetry. Sodium hydroxide 60 mM gave the best growth, maximizing average carbon consumption to 691.8 mg.L-1 and biomass production to 598.3 mg.L-1. The utilization of NaOH in the medium did not increase the metabolites content, except for protein. Carbohydrate was the dominant metabolite among the others. Fatty acids profile mainly composed of C16 and C18 fatty acids, which are favorable for biodiesel production. These results gave an overview of the potency of microalgae C. sorokiniana as a CO2 mitigation agent and alternative sources of energy and nutrition.